From Cell‐Derived Vesicles to Hybrid Nanovectors: Biological Membranes as Functional Blueprints for Gene Delivery - Clara Baldari; Claudia Leone; Gabriella Leccese; Claudia De Stradis; Alessandra Invidia; Concetta Quintarelli; Biagio De Angelis; Franco Locatelli; Giuseppe Gigli; Gabriele Maiorano; Ilaria Elena Palamà (Advanced Healthcare Materials, 2026)
ABSTRACT Nonviral gene therapy reached unprecedented clinical prominence, with the approval of lipid nanoparticles (LNPs). Yet, their success remains largely confined to a narrow range of applications and tissues, which reflects the inherent functional constraints based on formulation optimization to overcome intrinsically complex physiological barriers. In contrast, biological membranes evolved to integrate immune evasion, targeting, intracellular trafficking, and membrane fusion within a single functional interface. In this review, we provide a mechanistic comparison between membrane‐derived vesicles (MDVs) and hybrid biomimetic systems. We critically examine MDVs from different biological sources, highlighting their unique advantages for gene delivery applications. We also focus on hybrid systems, which merge the biological functionality of naturally derived membranes with the design control of synthetic nanovectors to address key limitations such as inefficient cytosolic release, poor targeting specificity, and transfection of hard‐to‐engineer cells. This review provides a biologically informed roadmap for designing efficient gene delivery vectors, proposing membrane‐integrated nanovesicles (NVs) as “living interfaces” for non‐viral gene therapy.